Peran Pendidikan Etika Kristen dalam Media Sosial di Era Disrupsi - Mesirawati Waruwu; Yonatan Alex Arifianto; Aji Suseno (Jurnal Pendidikan Agama Kristen (JUPAK), 2020)
The limitless development of social media, its meaning and function have begun to shift, no longer as a means of establishing relationships, communication, but at the stage of losing the role of ethics and morals, even disputes have occurred triggered by debates from communicating in social media. The purpose of this study is to describe the role of Christian ethics education in relation to the impact of social media development in the era of disruption. Using descriptive qualitative methods with literature literature can find solutions for believers in facing moral decadence due to social media abuse by knowing the era of disruption and ethical challenges from the wrong use of social media can affect moral decadence so that Christian ethics education on a biblical basis can bring modern humans. Believers in particular have become bright in social media and their use in accordance with Christian faith in this era of disruption.